Kolaborasi Dosen dan Mahasiswa STIKes Muhammadiyah Ciamis dalam Program Khitanan Massal sebagai Upaya Promotif dan Preventif Kesehatan Anak - Andan Firmansyah; Dadi Hamdani; Elis Roslianti; Ade Fitriani; Asep Gunawan; Suhanda Suhanda; Dedi Supriadi; Rudi Kurniawan; Nur Hidayat; Henri Setiawan; Irpan Ali Rahman; Ayu Endang Purwanti (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2026)
Introduction: Circumcision is one of the health interventions that provides medical, hygienic, and psychosocial benefits for children. However, not all families have adequate access to safe and affordable circumcision services. Community service activities conducted by higher education institutions represent a strategic effort to improve public health while implementing the Tri Dharma of Higher Education. Objective: This community service aimed to provide safe, free circumcision services for children while enhancing community access to quality healthcare through collaboration between lecturers and students of STIKes Muhammadiyah Ciamis. Method: This activity employed a community service approach involving the stages of planning, participant registration, health screening, circumcision procedures, health education, and post-circumcision follow-up. The program was implemented through collaboration between lecturers, nursing students, healthcare professionals, and local stakeholders. A total of 49 children from several villages and sub-districts in Ciamis Regency participated in the mass circumcision program. Result: The community service program was successfully implemented with all registered participants receiving circumcision services according to standard medical procedures. Participants originated from multiple areas in Ciamis Regency, indicating broad community participation and positive acceptance of the program. In addition to circumcision services, parents received education regarding wound care, infection prevention, nutrition, and post-circumcision activity restrictions. The collaboration between lecturers and students also provided valuable experiential learning in community nursing practice, communication, teamwork, and professional service delivery. Conclusion: he mass circumcision program effectively increased community access to safe circumcision services and demonstrated the important role of higher education institutions in improving community health. Collaboration between lecturers, students, healthcare workers, and local stakeholders represents an effective model for sustainable community service programs.